The Perspectives Of The Establishment Of International Financial Centers In Uzbekistan And The Implementation Of English Law (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article analyzed main notions of international financial center and its brief history, and the views of several scientists from different countries about international financial centers and its types. Moreover, it is also researched the perspectives of the establishment of international financial centers as one type of free economic zones in Uzbekistan. In addition, in this article researched the main features of common law, its implementation as a special legal regime on regulating international financial centers in Uzbekistan. As result of analyzes, it is illustrates legal, financial and other potential of establishment common law based international financial center as a type of free economic zone in Uzbekistan.